A práxis psicossocial em comunidade Ribeirinha da Amazônia: riscos e potência - Sanchez, Beatriz Marques (2021)
This article seeks to contribute to the development of the psychosocial praxis with traditional communities and, more specifically, with riverine communities from the Amazon. We are living in a historical and political time that exposes the urgent need to create references and tools able to guide our practice towards health in an ethicalpolitical dimension – which incorporates happiness, autonomy and social participation. The objective of this research is to describe and reflect on the possible directions of a practice oriented by the Research-Action-Participant’s methodological contributions, identifying it’s lapses and tools, and using two practices that were held on the Nazaré community (RO) as subject of analysis: The woman’s group around art, and psychosocial reception. The records were done through photography and field diary, seeking to build, in a dialectical way, knowledge and ways of doing. The theoretical references used come from the critical and dialectical Social Psychology perspective of Bader Sawaia, Silvia Lane, Lev S. Vigotski, and Baruch Espinosa’s theory of emotions. From the analysis of the processes, it became possible to identify the social inclusion/exclusion dialectics, which pervades the social insertion of riverine communities on Brazilian society, as well as the ethical-political suffering that results from it: political invisibility and constant violations of their bodies-territories, besides the lack of respect for their knowledge, lifestyle and cosmovision. This context produces affections such as shame, which weakens the body’s capacity to act, as well as the mind’s capacity to search for appropriate ideas. For that matter, the encounters strived to build, together with the participants, spaces of reflections and affections different from those produced by the context of exclusion and violence. The analyzes demonstrate the importance of the sense of common for the individual and collective strengthening of the participants, towards resistance against political domination and suffering. Art is highlighted as the big potentiator of ethical-political health, while a goal for the psychosocial practice